1991
DOI: 10.1242/jcs.100.2.339
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and transport of lysosomal α-glucosidase in the human colon carcinoma cell line Caco-2: Secretion from the apical surface

Abstract: The human adenocarcinoma cell line Caco-2 was used for studies on the biosynthesis and transport of lysosomal acid alpha-glucosidase in polarized epithelial cells. Metabolic labelling revealed that in Caco-2 cells alpha-glucosidase is synthesized as a precursor form of 110 × 10(3) Mr. This form is converted into a precursor of slightly higher Mr (112 × 10(3)) by the addition of complex oligosaccharide chains. Via an intermediate form of 95 × 10(3) Mr, this precursor is processed into a mature form of 76 × 10(3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Klumperman et al showed that a-glucosidase was secreted from the apical membrane of Caco-2 cells. 25 Meanwhile, as described in the Materials and methods section, to obtain RG, ESG was treated with a-amylase. Although a-amylase is an endo-acting enzyme and a-glucosidase is an exo-acting enzyme against glucan, aamylase seemed to trim off only the peripheral parts of the ESG molecules in the previous report.…”
Section: Discussionmentioning
confidence: 99%
“…Klumperman et al showed that a-glucosidase was secreted from the apical membrane of Caco-2 cells. 25 Meanwhile, as described in the Materials and methods section, to obtain RG, ESG was treated with a-amylase. Although a-amylase is an endo-acting enzyme and a-glucosidase is an exo-acting enzyme against glucan, aamylase seemed to trim off only the peripheral parts of the ESG molecules in the previous report.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we conclude that most probably, kojibiose is not easily taken up by enterocytes as such and therefore, has a high chance of reaching the intestinal microbiota in relatively high concentrations, which is a requirement for prebiotic activity. Yet, it needs to be noted that Caco-2 cells are able to secrete α-glucosidases at their brush-border side and that kojibiose can be cleaved by rat rodent α-glucosidases . In our assay, the α-glucosidase activity of the Caco-2 cells was not measured, and therefore, its concentration may be too low to see effects.…”
Section: Resultsmentioning
confidence: 97%